Antioxidant and Wound Healing Potential of Vitis vinifera Seeds Supported by Phytochemical Characterization and Docking Studies - Tarfah Al‐Warhi; Eman Maher Zahran; Samy Selim; Mohammad M. Al‐Sanea; Mohammed M. Ghoneim; Sherif A. Maher; Yaser A. Mostafa; Faisal Alsenani; Mahmoud A. Elrehany; Mohammed S. Almuhayawi; Soad K. Al Jaouni; Usama Ramadan Abdelmohsen; et al. (2022)
This study explored the in vivo wound healing potential of Vitis vinifera seed extract using an excision wound model with focus on wound healing molecular targets including TGFBR1, VEGF, TNF-α, and IL-1β. The wound healing results revealed that V. vinifera seed extract enhanced wound closure rates (p < 0.001), elevated TGF-β and VEGF levels, and significantly downregulated TNF-α and IL-1β levels in comparison to the Mebo®-treated group. The phenotypical results were supported by biochemical and histopathological findings. Phytochemical investigation yielded a total of 36 compounds including twenty-seven compounds (1−27) identified from seed oil using GC-MS analysis, along with nine isolated compounds. Among the isolated compounds, one new benzofuran dimer (28) along with eight known ones (29−36) were identified. The structure of new compound was elucidated utilizing 1D/2D NMR, with HRESIMS analyses. Moreover, molecular docking experiments were performed to elucidate the molecular targets (TNF-α, TGFBR1, and IL-1β) of the observed wound healing activity. Additionally, the in vitro antioxidant activity of V. vinifera seed extract along with two isolated compounds (ursolic acid 34, and β-sitosterol-3-O-glucopyranoside 36) were explored. Our study highlights the potential of V. vinifera seed extract in wound repair uncovering the most probable mechanisms of action using in silico analysis.